Preservation and Sustainability of Industrial Heritage in the Urban Renewal: A Case Study of Iec Long Firecracker Factory in Taipa, Macao - Zhu, Rong; Pinheiro, Francisco Vizeu (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
As an incomparable implication of industrial culture, the industrial heritage has a wide range of historical, technological, social, architectural or scientific values. With the process of large-scale contemporary urban revitalization, abandoned industrial buildings and areas always become the targets of urban renewal and redevelopment due to the ongoing transformation on structural changes of economy and adjustments of plot usage. Although the research and discussion on preservation of industrial heritage have been launched in the fields of theory and practice in China, many former industrial areas and buildings are still undergoing extreme threats and irreversible damages. Taking Iec Long Fireworks Factory which is the only well preserved survivor of industrial heritage in Macao as a case study, this paper presents its historic background, present challenges and future envisions of development. Based on group investigations and SWOT analysis, integrated strategies are proposed to preserve and revitalize the old factory ruins and their landscape settings. The conclusions show the significance to preserve and reuse industrial heritage opened for the urban renewal, which also could be a good contribution for sustainability of history and culture, environment, society and tourism.
Keywords: Architecture; Buildings; Cultural differences; Fires; History; International Committee; Production facilities